Precariedade urbana e necessidades sociais: condições de vida e de moradia no Conjunto Residencial Flor de Jasmim/Osasco (Programa Minha Casa Minha Vida) - Carpanelli, Fernanda Galhardo (2015)
This master s thesis raises questions about social needs and living conditions of the population that lives in Jasmim Flor residencial complex, first undertaking built in Osasco town SP through the government project Minha Casa Minha Vida - MCMV (My House My Life). The analytical construction is composed of three chapters and includes historical elements of the development of the living Brazilian politics, articulating these processes to the current scenario and its effects in the city dynamics. Recovering the story of Osasco territory s consolidation and its constitution as a town from São Paulo state in order to introduce the urban precariousness problematic that describes the current cycle of capitalist accumulation. It also sends a sign that the actions developed by the town in the area of living and urban politics, mainly among the years 2005 to 2014. The qualitative research shows the living conditions from the families in their originally territory, and the current housing, from significant statements from 50 habitants of the Residential Complex. The results indicate the living needs related to the access of a quality and suitable housing for the families; to the set of public services and trading surrounding the housing. To the work, wage and education, in order to support their new life condition, living cost and their needs in their interaction area, that demands in their everyday life, the construction of a new sociability, new relationships, as a consequence of an address change and territory. The path carved by the research has as its context the creation of MCMV and a critique of their formulations, their proposals and results in nationwide, for this reason the stories engender not only specific analyses of the situation studied, but they perform productive dialogues with significance and the effects that the program has been bringing to the urban process in progress in the country